Web module on nuclear disaster mitigation using ENACT Model: An effort to enhance student social responsibility - Nisa Andini; Sri Latifah; Antomi Saregar; Rahma Diani (Momentum: Physics Education Journal, 2025)
Past failures in nuclear technology have highlighted the essential role of society in mitigating radiation impacts and ensuring proper oversight. To enhance awareness and understanding, especially among students, about the effects of technological failures and the necessary mitigation measures, more effective and efficient education is needed. This study aims to develop a web module based on the ENACT (Engage, Navigate, Anticipate, Conduct, and Take Action) model designed to enhance students' social responsibility. Social responsibility is a critical aspect that every individual in society should possess, particularly in addressing and mitigating nuclear disasters that require deep knowledge and high social awareness. Through the Socio Scientific Issues (SSI) approach, this web module integrates theoretical and practical aspects of learning, enabling students not only to comprehend the concepts of radiation physics but also to develop a responsible attitude towards society and the environment. This research employs a research and development (R&D) method encompassing analysis, design, development, implementation, and evaluation phases. The results indicate that the use of the ENACT model in this web module is effective in fostering students' social responsibility, as evidenced by their improved understanding of radiation physics and active engagement in discussions and simulations of nuclear disaster mitigation. The implications of this study highlight the importance of integrating educational technology with character development to produce a generation that is competent and socially responsible in facing global challenges.